2002
DOI: 10.1038/sj.onc.1205882
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional corepressor MTG16a contains a novel nucleolar targeting sequence deranged in t (16; 21)-positive myeloid malignancies

Abstract: The MTG (Myeloid Translocation Gene) proteins are a family of novel transcriptional corepressors. We report that MTG16a, a protein isoform encoded by the MTG16 gene deranged by the t (16; 21) in myeloid malignancies, is targeted to the nucleolus. The amino acid sequence necessary for nucleolar localization was mapped to the MTG16a N-terminal region. MTG16a, like MTG8, the nuclear corepressor deranged by the t (8; 21), is capable to interact with specific histone deacetylases (HDACs) suggesting that the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…Apparently, loss of the N-terminus of MTG16 has profound biological consequences on myeloid cell growth. We previously hypothesized a critical role for the N-terminus of MTG16 based on the observation that exogenous MTG16D2 had a different intranuclear localization than exogenous MTG16 in COS cells (Hoogeveen et al, 2002). However, we were unable to show different intranuclear localization for these two proteins in 32D/ WT1 cells.…”
Section: Discussionmentioning
confidence: 38%
See 3 more Smart Citations
“…Apparently, loss of the N-terminus of MTG16 has profound biological consequences on myeloid cell growth. We previously hypothesized a critical role for the N-terminus of MTG16 based on the observation that exogenous MTG16D2 had a different intranuclear localization than exogenous MTG16 in COS cells (Hoogeveen et al, 2002). However, we were unable to show different intranuclear localization for these two proteins in 32D/ WT1 cells.…”
Section: Discussionmentioning
confidence: 38%
“…As mentioned, we previously found that AML1-MTG16 can interact with histone deacetylases (HDACs) (Hoogeveen et al, 2002). This led us to hypothesize that AML1-MTG16 is capable of inducing epigenetic repression of endogenous AML1 target genes by tethering, via the MTG16 moiety, HDACs at AML1-target sites.…”
Section: Aml1-mtg16 Induces Downregulation Of Endogenous Aml1-target mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a common translocation in AML patients, t(8;21) results in the generation of fusion protein AML1 and ETO (eight-twenty-one or MTG8), which also recruits corepressors and HDACs by the C terminus of ETO, leading to repression of the AML1 target genes (Rowley, 1982;Erickson et al, 1992;Gelmetti et al, 1998;Lutterbach et al, 1998;Wang et al, 1998;Amann et al, 2001). Analogous effect has been described for the fusion protein MTG16a-AML1, resulting from the t(16;21) translocation, present in a number of AML patients (Gamou et al, 1998;Hoogeveen et al, 2002).…”
Section: Hdac3 In Leukemiamentioning
confidence: 90%